On the (im)possibility of improving upon the student-proposing deferred acceptance mechanism - Onur Kesten; Morimitsu Kurino (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2012)
This paper studies a general school choice problem with or without outside options. The Gale-Shapley student-proposing deferred acceptance mechanism (DA) has played a central role not only in theory but also in important practical applications. We show that in problems where some students cannot credibly submit a single school as the only acceptable option, it is possible to improve upon DA without sacrificing strategyproofness. On the other hand, in unrestricted problems where no outside options necessarily exist, it is not possible to improve upon DA via a strategy-proof mechanism. – – Es wird ein allgemeines school-choice-Problem untersucht mit und ohne outside options. Der Gale-Shapley student-proposing deferred acceptance-Mechanismus (DA) spielt eine zentrale Rolle nicht nur in der Theorie sondern auch in wichtigen praktischen Anwendungen. Wir zeigen, dass in Situationen, in denen einige Schüler nicht glaubwürdig nur eine einzige Schule als akzeptable Option angeben können, der DA verbessert werden kann, ohne dass die Nichtmanipulierbarkeit (strategy proofness) des Mechanismus dafür geopfert werden muss. Auf der anderen Seite gilt für Situationen, in denen nicht notwendigerweise outside options existieren, dass der DA nicht verbessert werden kann mit Hilfe eines nichtmanipulierbaren Mechanismus.
Keywords: C78; D78; I21; 330; student-proposing deferred acceptance mechanism; strategy-proofness; Pareto dominance; outside options; Schulauswahl; Matching; Shapley-Wert; Schule; Quotenregulierung; Theorie; USA